Can Regenerative Agriculture in Andean Potato Farming Enhance Productivity, Profitability, and C Sequestration While Reducing Carbon Footprint? A Case Study from Northern Peru - Briceño, P.; Ninanya, J.; Seminario, J.F.; Otiniano, R.; Rinza, J.; Mestanza, C.; Arias, E.; Villanueva, C.; Mendoza, W.; Mendiburu, F. de; Kreuze, Jan F.; Ramirez, D. (2025)
Andean agriculture faces several challenges such as land use changes, land degradation, poverty, extreme events, and climate change. Such conditions compromise food production and security, highlighting the need to explore sustainable alternatives. This two-trial study evaluated the potential of regenerative agricultural practices for potato production in the Peruvian Andes over two seasons (2022–2024), in terms of productivity (FTY: Fresh tuber yield), profitability (BCR: Benefit-cost ratio), C footprint (CF), and soil properties. One trial (Trial 1) tested tillage practices—minimum (MT) vs. zero (ZT); plastic barriers—with (PL) vs. without (NP); and mulch thicknesses—0.1 (M10) vs. 0.2 (M20) vs. 0.3 (M30) m. The other trial (Trial 2) tested cropping systems—monoculture (NI) vs. intercropping with faba bean (IN); a fungicide optimization tool—with (DI) vs. without (ND); and chicken manure application rates—1 (CM1) vs. 2 (CM2) vs. 4 (CM4) t ha−1. Compared to conventional practices, MT+NP+M30 increased FTY by ~3.5% and reduced CF by 19.9% in Trial 1, while NI+DI+CM4 increased FTY and BCR by 28% and 12.4%, respectively, in Trial 2. ZT and IN performed poorly in the short-term Andean context, suggesting the need for further long-term studies. In both trials, short-term effect of regenerative practices improved soil organic matter with a mixed effect on pH. Regenerative practices in the Andes offer synergies and trade-offs, but integrating reduced tillage, mulching, and organic fertilization can enhance sustainability without reducing productivity. Long-term adoption is essential to restore soil carbon stocks, enhance sustainability, and increase the resilience of Andean agriculture.